Amy's view - Hare, David, 1947- (London : Faber and Faber, 1997)
Esme Allen is a well-known West End actress at just the moment when the West End is ceasing to offer actors a regular way of life. A generational play about the long term struggle between a strong mother and her loving daughter, Amy's View mixes love, death and the theatre in a way which is both heady and original
"FF plays"--Cover.
ENH
The WORM
Keywords: Actors -- Drama; Mothers and daughters -- Drama; English literature; London (England) -- Drama